Determinant Of Halal Industry Product Selection - Feri Dwi Riyanto; Ikhsan Maksum; Naufal Dzakwana (Universitas Muhammadiyah Prof. DR HAMKA., 2020)
This paper aims to analyze the determinants of Malang people's perceptions in choosing the halal industry. In this study, using product knowledge, accessibility, and information/promotion as exogenous variables, while religious and the perception of the halal industry as an endogenous variable and also halal Certification as a moderating variable. The government has prepared a masterplan to develop the halal industry. One of the goals of the government in making a masterplan is to foster public perceptions of the halal industry. So that is expected to be able to encourage the growth and development of the halal industry market in Indonesia, which is meant by the halal industry, including halal tourism, halal culinary, and halal hotels. Data's collected through a questionnaire of 160 respondents. This research uses the Partial Least Square (PLS) method based on variants approach. The results showed that all exogenous variables influence the endogenous variable, except information that does not significantly influence the religious and product knowledge also does not significantly influence the perception of the halal industry. While the halal certification variable as a moderating does not have a weakening or strengthening effect on the other variables.